PENGARUH CUSTOMER EXPERIENCE DAN TRUST TERHADAP REPURCHASE INTENTION TIKET KERETA API - Ain, Qurotul; Azizah, Azizah; Nurkhayati, Isnaini; Zaenuddin, Achmad (Politeknik Negeri Semarang, 2024)
PT KAI is the only company that provides rail transportation services in Indonesia. PT KAI has 9 Operational Areas (Daop) spread across Java Island. PT KAI Daop 4 Semarang oversees stations on the northern rail line in Central Java. This study aims to determine the influence of customer experience and trust on repurchase intention. The samples of this study were 100 respondents from PT KAI Daop 4 Semarang train passengers who had made a ticket purchase transaction and used the train as transportation at least twice. The sampling technique used in this study is nonprobability sampling. Data analysis used multiple linear regression with IBM SPSS 25. The data obtained was collected from questionnaire and literature review based on predetermined indicators. The results of the analysis show that customer experience and trust have an influence on repurchase intention. The magnitude of the coefficient of determination is 0.582, which means that customer experience and trust contribute 58.2%, while the remaining 41.8% is contributed by other variables not examined in this study. This implies that the customer experience experienced by passengers shows positive results and the trust that has been built by the company has an important role in repurchase intention.